2003
DOI: 10.1002/ptr.1216
|View full text |Cite
|
Sign up to set email alerts
|

Main flavonoids in the root of Scutellaria baicalensis cultivated in Europe and their comparative antiradical properties

Abstract: The content of the main flavonoids in the root of Scutellaria baicalensis Georgi cultivated in Central Europe was evaluated using the new simple RP-HPLC method with gradient of acetonitrile in mobile phase. The main components of the roots were baicalin (8.12% of dry root mass) and wogonin glucuronide (2.52%). The content of flavonoids was comparable with the content in plants cultivated in natural localities. Five main flavonoids were evaluated for their scavenging ability with DPPH radical-generating system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…A previous study showed that a scavenger for ROS suppressed urinary protein and the proliferation of mesangial cells in thy-1 nephritis [27]. Since flavonoids in the root of Scutellaria baicalensis cultivated in Europe, which a common herb in TJ-9, TJ-96, and TJ-114, which have anti-oxidant activity [28], it is suggested that these flavonoids, including baicalin, oroxylin A, and woogonin in figure 1, suppressed this experimental nephritis by their anti-oxidative action. To evaluate the oxidative status in the glomeruli, SOD-activity of a renal cortex homogenate was measured.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that a scavenger for ROS suppressed urinary protein and the proliferation of mesangial cells in thy-1 nephritis [27]. Since flavonoids in the root of Scutellaria baicalensis cultivated in Europe, which a common herb in TJ-9, TJ-96, and TJ-114, which have anti-oxidant activity [28], it is suggested that these flavonoids, including baicalin, oroxylin A, and woogonin in figure 1, suppressed this experimental nephritis by their anti-oxidative action. To evaluate the oxidative status in the glomeruli, SOD-activity of a renal cortex homogenate was measured.…”
Section: Discussionmentioning
confidence: 99%
“…It has a particularly high content of flavonoids, which are modifiers of inflammatory processes, prevent bacterial infections and have antiviral, antitumor and antioxidative properties as well as hepatoprotecive effects (Gao et al, 1999;Chan et. al., 2000;Bochorakova et al, 2003). The objective of this study was to evaluate the effect of SCR on the performance of broiler chickens and selected blood parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Among the herbal drugs contained in GHGZT, Scutellariae radix [6] and Panax ginseng [11] have been used extensively, and their clinical efficacies have been documented in regard to anti-ulcer activity. The flavonoids of Scutellariae radix have been found to be free radical scavengers [3]; free radicals play an important role in ulcerative and erosive lesions of the gastrointestinal tract. Glycyrrhizae radix water extract and its two major constituents, glycyrrhizin and 3-glycyrrhetinic monodesmoside, may be promising for amelioration of hypoxia (ischemia)-reoxygenation (reperfusion) injury and improvement of renal function by acting as antioxidant and oxygen radicalscavenging agents [32].…”
mentioning
confidence: 99%